Biomarkers in Hepatic Disease: A Review Focused on Critically Ill Patients - ERTÜRK ŞENGEL, BUKET (SAGE Publications Inc., 2016)
The ability to make a diagnosis early and appropriately is paramount for the survival of the critically ill ICU patient. Along with the myriad physical examination and imaging modalities available, biomarkers provide a window on the disease process. Herein we review hepatic biomarkers in the context of the critical care patient. © The Author(s) 2014.
Keywords: biological markers; critical illness; ICU; intensive care unit; liver disease; serum proteins